Efficient method for the computation of parasitic coupling in microwave integrated circuits - McPhee, Dave (University of Ottawa (Canada), 2005)
Higher integration and smaller layout size, two major trends in today's industry, lead to more prominent parasitic electromagnetic coupling effects in high-frequency communication systems. Using network theory concepts and de-embedding techniques, this thesis presents a fast and efficient method to model such coupling in microwave integrated circuits, making the design more reliable. The efficiency of the new technique is demonstrated through examples of circuit simulations and circuit optimization.
Keywords: Engineering, Electronics and Electrical.